1991
DOI: 10.1111/j.1348-0421.1991.tb02030.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Properties of Borrelia burgdorferi Isolated from the Ixodes ovatus in Shizuoka, Japan

Abstract: Three strains of spirochetes (IKA1 to 3) were isolated from the midgut of Ixodes ovatus collected in the Ikawa region of the northern part of Shizuoka, Japan. These isolates had eight flagella, and their size and other morphological features were similar to Borrelia burgdorferi. They showed similar motility and reacted with monoclonal antibody (MAb) H9724 against borrelial flagella and with MAb H5332 against the outer surface protein A. These strains showed similar SDS-PAGE profiles to that of B. burgdorferi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
0
12
1
1
Order By: Relevance
“…The Borrelia species identity as determined by antigenic differences has been suggested to correlate with the origin of ticks. In Japan, isolates from I. ovatus were different from those of I. persulcatus (8,24,25,33). In our survey, it may be suggested that I. ovatus and H. flava can acquire spirochetes by feeding on a same deer affected with I. persulcatus.…”
Section: Discussionmentioning
confidence: 81%
“…The Borrelia species identity as determined by antigenic differences has been suggested to correlate with the origin of ticks. In Japan, isolates from I. ovatus were different from those of I. persulcatus (8,24,25,33). In our survey, it may be suggested that I. ovatus and H. flava can acquire spirochetes by feeding on a same deer affected with I. persulcatus.…”
Section: Discussionmentioning
confidence: 81%
“…Fresh isolates were obtained from culture of midgut from adult ticks of I. ovatus collected by flagging in the Ikawa region in the northern part of Shizuoka. Methods for tick collection and isolation of Borrelia were described previously (19). The strains were cultivated at 33 C in Barbour-Stoenner-Kelly II (BSK II) medium (3).…”
Section: Methodsmentioning
confidence: 99%
“…burgdorferi sensu lato was isolated from ixodid ticks, I. persulcatus (20,24), I. ovatus (19,20,25), other ixodid ticks (28), wood mouse (Apodemus speciosus ainu; 24), long-tailed shrew (Sorex unguiculatus; 30) and patients with erythema migrans (EM; 26) in Japan. Interestingly, isolates from I. ovatus were homologous with respect to the molecular weight of Osp A (27), and RFLP in 23S rRNA gene (31).…”
mentioning
confidence: 99%
“…Virulence and infectivity of B. japonica to human is not determined yet. Despite of many cases suffering I. ovatus bite, only one suspected case has been reported in Japan (18). Susceptibility of clinical isolates from EM (JEM1-JEM8) to three antibiotics, amoxicillin, erythromycin and minocycline, by which efficacy against four Japanese isolates, 12-92 vi, HP1 vi, NP81 vi, and NO129-6E, were proven as mentioned above, was examined.…”
mentioning
confidence: 99%
“…Borrelia was isolated from ixodid ticks, I. persulcatus (19,21), I. ovatus (18,21), other ixodid ticks (22), wood mouse (Apodemus speciosus ainu; 23), long-tailed shrew (Sorex unguiculatus; 24) and skin lesion of erythema migrans (EM) of patients (20). B. japonica, a new species, isolated from I. ovatus and long-tailed shrew was described on the basis of genomic DN A hybridization analysis and restriction fragment length polymorphism analyses of the flagellin structural genes and the 16S rRNA genes (17).…”
mentioning
confidence: 99%